Effects of online education on interpreting courses: Challenges, downsides and opportunities - UYANIK, GÖZDE BEGÜM (My University, 2023)
The world faced with compulsory online distance education system in 2020 as a consequence of COVID-19 pandemic. Thus, there occurred the need for the revision of course models as well as teaching methods of the educators at the time, and their integration into the online platforms. Online platforms also paved the way for some adjustments within the fields of education and business. Staying at home, being isolated, and not being able to get together in a globalized world with some sort of restrictions brought about remote (online) interpreting services offered by those platforms, which started to be widely used for making the international businesses keep running. Some of them even offered free use of services for their users for education purposes only. As a result, educators offering interpreting courses in undergraduate programs of translation and interpreting departments in the universities benefited from both of these adjustments, as interpreting practice by its very nature stood between those two. They combined the services offered in business as well as education; therefore, successfully conducting online interpreting courses, where interactive student participation was a must. After a year of providing interpreting courses online and experiencing both the advantages and disadvantages of this new system during the pandemic, educators had to re-adapt the interpreting courses having provided online into the in-class environment; as a result, they faced new challenges. This paper discusses the downfalls and opportunities specifically encountered in interpreting courses offered both in-class and online environments at undergraduate level. It is claimed that combining useful practices as well as teaching models applied in those environments together has changed the way how interpreting courses could be offered permanently. This study presents the techniques used in Introduction to Interpreting I and Introduction to Interpreting II courses conducted online for the academic year 2021-2022 and in-class for the academic year 2022-2023 at the Department of English Translation and Interpreting, Marmara University in Türkiye. It also discusses the techniques used in terms of their (in)applicability for in-class and/or online environments by providing the reasons why. Moreover, the study presents the feedbacks gathered from the undergraduate students who took the aforementioned interpreting courses offered during the specified academic years. As a result, the paper offers a hybrid course plan for Introduction to Interpreting courses in the post-pandemic era. Keywords: interpreting, remote interpreting, course plan, post pandemic teaching models, online platforms
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Mütercim-Tercümanlık; İngilizce Mütercim-Tercümanlık; Social Sciences and Humanities; Philology; Interpreting and Translating; English Interpreting and Translating; Sanat ve Beşeri Bilimler (AHCI); Sosyal Bilimler (SOC); Sanat ve Beşeri Bilimler; EDEBİYAT; Arts & Humanities (AHCI); Social Sciences (SOC); ARTS & HUMANITIES; LITERATURE; Edebiyat ve Edebiyat Teorisi; Sosyal Bilimler ve Beşeri Bilimler; Literature and Literary Theory; Social Sciences & Humanities